2012
DOI: 10.1088/0029-5515/52/2/023001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of particle recycling in the TEXTOR helical divertor

Abstract: Abstract. The TEXTOR helical divertor is a magnetic configuration created by the application of external resonant magnetic perturbations (RMPs) with the intention to control plasma edge transport and the resulting particle and heat fluxes to the divertor target. It is confirmed by 3D computer simulations that no high-recyclinglike regime is established under TEXTOR relevant conditions, despite the fact that a transition to detachment (i.e. a saturation or even a roll-over of the recycling flux) is observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“… ), as discussed inFig.1, as well as with the convection flux ( upstream ionization source, are responsible for the modification of this density regime[61]. The effect of convection energy flux was also pointed out in ref [62]…”
mentioning
confidence: 56%
“… ), as discussed inFig.1, as well as with the convection flux ( upstream ionization source, are responsible for the modification of this density regime[61]. The effect of convection energy flux was also pointed out in ref [62]…”
mentioning
confidence: 56%
“…For the process of loss of parallel momentum, we consider a frictional interaction between counter-streaming flows, which are created in the edge region due to the magnetic field structure. It is found, from the numerical simulations in various devices, that the counter-streaming flow are formed not only in island divertors, but also in the stochastic layer of LHD [63], TEXTOR-DED [105], Tore Supra [111], DIII-D [112] and ITER [29]. It is also found that all these flow structures are regulated by the main poloidal mode number, m , of the perturbation field in the poloidal cross section.…”
Section: Estimation Of M  the  -Distance Between The Counter-strementioning
confidence: 99%
“…It is seen that under high density and low temperature condition the  -energy flux (the first term in eq. (3)) can provide a channel through which the //-energy flux (the second term) can be reduced.In ref [105],. the replacement of //-energy flux ( e q // ) with the convection flux ( substantial upstream ionization source, is also discussed as a cause for the density regime modification.…”
mentioning
confidence: 99%
“…20,21 This code applies a fluid transport model for the edge plasma, which is coupled to a kinetic transport model for neutral particles. Originally developed for stellarators, it has also been used to study 3D effects by RMPs at the TEXTOR tokamak 4,[22][23][24] and then generalized for the application in poloidally diverted tokamak configurations. 25 After a short description of the input parameters for this code, the resulting impact of RMP screening on the edge plasma, in particular on particle and heat fluxes to the divertor targets, is discussed.…”
Section: Introductionmentioning
confidence: 99%